2009
DOI: 10.1097/scs.0b013e3181bf85f4
|View full text |Cite
|
Sign up to set email alerts
|

Location of Mental Foramen Based on Soft- and Hard-Tissue Landmarks in a Chinese Population

Abstract: The purpose of the present study was to determine the location of the mental foramen (MF) based on soft- and hard-tissue landmarks, to facilitate prediction of the location of this structure during facial and dental surgery. Forty-two hemispheres of 21 adult cadavers (16 men and 5 women; aged 30-75 years) were dissected to expose the MF. The locations of the MFs were evaluated with direct and photographic measurements. Most of the MFs presented a single foramen (95%), except for only 2 cases with double forami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 9 publications
5
27
0
4
Order By: Relevance
“…Ignoring the presence of an AMF may cause unexpected damage to the neurovascular bundles or lead to the failure of a mental nerve block. In the present study, AMF were found in 5.81% of patients, which was similar to the 5% incidence reported in a previous study in a Chinese population [5]. The incidence of AMF appears to vary among ethnic groups; Mwaniki et al reported multiple foramina in 4.5% of an African population [17], Kalender et al observed AMF in 6.5% of a Turkish population [18], and incidences of 6.68% and 7% were found in Greek [19] and Japanese [20] populations, respectively.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Ignoring the presence of an AMF may cause unexpected damage to the neurovascular bundles or lead to the failure of a mental nerve block. In the present study, AMF were found in 5.81% of patients, which was similar to the 5% incidence reported in a previous study in a Chinese population [5]. The incidence of AMF appears to vary among ethnic groups; Mwaniki et al reported multiple foramina in 4.5% of an African population [17], Kalender et al observed AMF in 6.5% of a Turkish population [18], and incidences of 6.68% and 7% were found in Greek [19] and Japanese [20] populations, respectively.…”
Section: Discussionsupporting
confidence: 79%
“…Thus, it is important to explore the precise position of the MF and its relationship with peripheral structures. However, previous studies of the MF, which were performed on human cadavers [5,6] or using panoramic radiographs [7,8], had some shortcomings. Sample sizes were relatively small, and the superimposition of structures on radiographs made it difficult to identify the three-dimensional (3D) relationships between the MF and root apices.…”
Section: Introductionmentioning
confidence: 99%
“…Dados que corroboram com os estudos de Manhães Jr et al (2009) Estudos realizados em diferentes grupos populacionais mostram que a localização do FM é predominantemente, abaixo do segundo pré-molar classe IV (APINHASMIT et al, 2006;KIM et al, 2006;GUO et al, 2009, SANKAR, BHANU, SUSAN, 2011SAITO, et al, 2015). A classe V, onde forame está localizado entre o segundo pré-molar e primeiro molar, foi observada em 10,5% dos casos (Tabela 2).…”
Section: Resultsunclassified
“…The overall mean distance lateral to the chelion was 3.4 mm bilaterally. Guo et al 22 indirectly measured the horizontal distance from the chelion to the mental foramen on digitalized photographs. A mean distance of 3.55 mm (SD 1.70 mm) mesial to the chelion in the frontal view and 7.19 mm (SD 3.03 mm) lateral to the chelion on the lateral view was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Only two prior studies described the position of the mental foramen in relation to soft tissue landmarks; however, both studies conducted their measurements on digitalized radiographs. 22,23 With tooth loss and wear, variation in hard tissue landmarks such as the premolar teeth are expected. 13,21 On the other hand, whilst it is noted that there is a decrease in facial skin turgor with advancing age, soft tissue landmarks such as the chelion are more likely to remain static and perhaps may even be more accurate when used as a landmark in locating the mental foramen.…”
Section: Introductionmentioning
confidence: 99%